Booster dose after 10 years is recommended following 17DD-YF primary vaccination. Issue 2 (1st February 2016) - Campi-Azevedo, Ana Carolina; Costa-Pereira, Christiane; Antonelli, Lis R; Fonseca, Cristina T; Teixeira-Carvalho, Andréa; Villela-Rezende, Gabriela; Santos, Raiany A; Batista, Maurício A; Campos, Fernanda M; Pacheco-Porto, Luiza; Melo Júnior, Otoni A; Hossell, Débora MSH; et al.
Abstract : A single vaccination of Yellow Fever vaccines is believed to confer life-long protection. In this study, results of vaccinees who received a single dose of 17DD-YF immunization followed over 10 y challenge this premise. YF-neutralizing antibodies, subsets of memory T and B cells as well as cytokine-producing lymphocytes were evaluated in groups of adults before (NVday0) and after (PVday30-45, PVyear1-4, PVyear5-9, PVyear10-11, PVyear12-13) 17DD-YF primary vaccination. YF-neutralizing antibodies decrease significantly from PVyear1-4 to PVyear12-13 as compared to PVday30-45, and the seropositivity rates (PRNT≥2.9Log10 mIU/mL) become critical (lower than 90%) beyond PVyear5-9. YF-specific memory phenotypes (effector T-cells and classical B-cells) significantly increase at PVday30-45 as compared to naïve baseline. Moreover, these phenotypes tend to decrease at PVyear10-11 as compared to PVday30-45. Decreasing levels of TNF-α + and IFN-γ + produced by CD4 + and CD8 + T-cells along with increasing levels of IL-10 + CD4 + T-cells were characteristic of anti-YF response over time. Systems biology profiling represented by hierarchic networks revealed that while the naïve baseline is characterized by independent micro-nets, primary vaccinees displayed an imbricate network with essential role of central and effector CD8 + memory T-cell responses. Any putative limitations of this cross-sectional study will certainly be answered by the ongoing longitudinal population-based investigation. Overall, our data support the current Brazilian national immunization policy guidelines that recommend one booster dose 10 y after primary 17DD-YF vaccination.